THE EFFECT OF THE CONCENTRATION OF SULFONATING AGENT ON THE CHARACTERISTICS OF SULFONATED BACTERIAL CELLULOSE MEMBRANES FOR DMFC APPLICATIONS - NAYLA (NIM :20514051), MAHDIYA
The increasing needs of energy has driven a number of researchers to seek alternative energies to substitute fossil fuels. One type among them currently being developed is DMFC (Direct Methanol Fuel Cell), a type of fuel cells which is much in demand because it uses methanol which is easy to store. Nowadays, most DMFC uses fluoropolymers as the polymer electrolyte membrane which contain branched chain sulfonate groups. This material is well-known by the trade mark of NafionÃ‚Â®. However, it has some weaknesses, such as its high cost and fairly high methanol permeability. In this research, bacterial cellulose membranes which have strong mechanical properties and high thermal stability are used as an alternative for polymer electrolyte membrane. This type of membrane is made of coconut water using Acetobacter xylinum bacteria. The optimization of the membrane is done using the sulfonation process in which the hydroxyl groups in the cellulose is replaced by the sulfonate (-SO3H) groups in order to make the polymer more hydrophilic. The sulfonation is done to increase the conductivity of the bacterial cellulose membrane. This research aims to determine the effect of chlorosulfonic acid concentration on the characteristics of sulfonated bacterial cellulose membranes. The sulfonation process used MAOS (Microwave Assisted Organic Synthesis) method with chlorosulfonic acid variation between 0.5 and 3%. The characterization of the membranes includes the analysis of functional mechanical properties of the membrane using tensile test, the swelling degree, proton conductivity, ion exchange capacity, membrane morphology using SEM (Scanning Electron Microscopy) and the determination of sulfur levels using EDS (Electron Dispersive X -Ray Spectroscopy). The results of the functional group analysis indicates the emergence of a peak at wave number 1335 cm-1, which shows an asymmetric vibration S=O of the sulfonate group. The mechanical properties of the membrane shows that the stress of the sulfonated bacterial cellulose membrane is inversely proportional to the percentage of chlorosulfonic acid. The higher the percentage of chlorosulfonic acid, the smaller the membrane stress.The sulfonated cellulose bacterial membrane strain is also proportional to the v percentage of chlorosulfonic acid. The swelling degree of the membrane is proportional to the percentage of chlorosulfonic acid used to sulfonate the membrane. This is due to the increasing number of -OH groups at C number 6 which is substituted by -SO3H group resulting in more hydrophilic membranes. Similar to the degree of swelling, the proton conductivity and the ion exchange capacity of the membranes is also likely to increase in proportion to the percentage of chlorosulfonic acid. The presence of the sulfonate groups in the membrane increases causing the proton exchange easier. Photos of the membrane surface by SEM shows the morphology of the membrane fibers. The content of sulfur on the surface of sulfonated bacterial cellulose membrane increases as the percentage of chlorosulfonic acid used is higher. Membrane with highest proton conductivity and ion exchange capacity is determined methanol permeability value. Methanol permeability of the membrane SBs-3 obtained of 2.75 x 10-6 cm2/s. It can be concluded from the experimental results that the bacterial cellulose membrane sulfonated by 3% chlorosulfonic acid has the optimum characteristics, namely a degree of swelling of 183.54%, a conductivity of 0.055 S/cm at 10 mV and 0.052 S/cm at 100 mV measurements, an ion exchange capacity of 3.88 meq/g and a percentage of sulfur content of 0.94% and methanol permeability of 2.75 x 10-6 cm2/s.